ChemInform Abstract: Synthesis of Internal Alkynes Through the Pd‐Catalyzed Coupling of Heteroaryl Halides with Terminal Alkynes. Issue 32 (18th July 2013) - Lu, Linhua; Yan, Hong; Sun, Peng; Zhu, Yan; Yang, Hailong; Liu, Defu; Rong, Guangwei; Mao, Jincheng
Abstract 3‐Bromo‐indole and 2‐bromo‐benzimidazole don′t give any traceable coupling products due to the occurrence of multiple side reactions as indicated by TLC.